(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
The present study was carried out for the isolation and molecular detection of duck plague virus (DPV) for the development of inactivated vaccine seed from the local outbreaks. A total of 12 suspected dead duck samples were collected from commercial farms and local market at Sunamganj, Netrokona and Mymensingh districts. Then, the samples were processed and prepared inocula were inoculated into 9-12 days old duck embryonated eggs. In duck embryonated eggs, several passages (3-4) were performed before infection into DEF cell culture. Presence of viral DNA was confirmed by PCR using the primer for DNA polymerase gene. After PCR confirmation, virus cultured in DEF cell was used for the preparation of formalin (0.12%) inactivated and oil based adjuvanted vaccine and was experimentally injected to 18 ducklings and 5 were kept as control. TCID50 of the selected virus for vaccine preparation was 108.70/ml. The mean passive haemagglutination assay (PHA) titre of sera of samples at 0 days, 7 days and 14 days post vaccination were 4.0±0, 14.22±1.78 and 44.44±4.4, respectively, which indicated significant (p<0.01) increase of antibody titre. Embryonated duck eggs and DEF cell culture are effective for virus isolation and on the basis of PHA test, it could also be suggested that the experimentally developed DP vaccine can be used successfully for the prevention of DP in Bangladesh. Asian Australas. J. Biosci. Biotechnol. 2018, 3 (1), 78-85